THE IMPORTANCE OF RENAL FUNCTION TESTS IN PEDIATRIC NEPHROLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Renal function tests are vital for evaluating kidney health and diagnosing various renal disorders in pediatric patients. These tests measure parameters that reflect the kidneys' ability to filter waste products, maintain fluid and electrolyte balance, and regulate metabolic processes. Key tests, such as serum creatinine, blood urea nitrogen (BUN), urine analysis, and glomerular filtration rate (GFR), are routinely used to assess kidney function and diagnose conditions such as acute kidney injury (AKI), chronic kidney disease (CKD), nephrotic syndrome, and glomerulonephritis in children. This article reviews the importance of renal function tests in pediatric nephrology and discusses the interpretation of results in diagnosing and monitoring kidney diseases.